PENERAPAN SANKSI PIDANA TERHADAP TELEVISI KABEL YANG TIDAK MEMILIKI IZIN DI KABUPATEN KAMPAR BERDASARKAN UNDANG-UNDANG NOMOR 32 TAHUN 2002 TENTANG PENYIARAN - Rayonnita Rayonnita; Mexsasai Indra; Ferawati Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Providing sanctions against cable television companies that do not have broadcast licenses is one of the crimes that harm some other businessmen. Application of legal sanctions for broadcast licenses based on Law Number 32 of 2002 concerning broadcasting licenses in Kampar Regency. Obstacles in law enforcement against broadcasting licenses based on Law Number 32 of 2002 concerning broadcasting permits. Efforts are being made to overcome barriers and law enforcement against broadcasting licenses based on Law Number 32 of 2002 concerning broadcasting licensesThis type of research is Sociological Law research, i.e. research by looking at the effectiveness of the validity of the law in the field other than that in this study the author immediately conducted a research location or place studied to provide a complete and clear picture of the problem under study. This research was conducted at the Krp Polisi Pekanbaru City Resort and the Riau Provincial Indonesian Broadcasting Commission. The population and sample are all parties related to the problem under study. Data sources used are: primary data, secondary data and tertiary data, data collection techniques using interviews and literature review.From the results of this study there are three main problems that can be concluded. First, the application of criminal sanctions against criminal acts of cable television that do not have broadcast licenses in kampar regency, even though the law enforcement process does not work in accordance with the provisions concerning Law Number 32 of 2002 concerning Broadcasting. Secondly, the weaknesses of the Regional Indonesian Broadcasting Commission in giving broadcast licenses due to problems both internally and externally within the organization of the Riau Province KPID relate to the role of the organization independently based on the Law and the decentralization of power related to the Law. Third, Overcoming the weaknesses of the Regional Indonesian Broadcasting Commission (KPID) Process, yes it does the effectiveness of Supervision of all cable television service providers in the region involving the Regional Broadcasting Commission (KPID) of Riau Province, Regional Government, and the Police to provide cable television services not to broadcast which is contrary to Broadcasting standards. The author's advice, First, It is better to apply criminal sanctions in the US to be sanctions only. Second, the dissemination of information by the Regional Indonesian Broadcasting Commission (KPID) on cable television in several districts. Third, make supervision effective for all institutions providing cable television services in the area.